2011
DOI: 10.1007/s00217-011-1544-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of roasting on phenolics composition and antioxidant activity of peanut (Arachis hypogaea L.) kernel flour

Abstract: The effects of roasting on the phenolics composition and antioxidant activity of peanut (Arachis hypogaea L.) kernel flour were appraised. Peanut kernel flour, with and without skin, were roasted at 160 °C for 10, 20, 30, 40 and 50 min. The resultant changes in the antioxidant activity of roasted peanut kernel flour were assessed by the determinations of total phenolics, 1,1-diphenyl-2-picrylhydrazyl free radical-scavenging capacity, percent inhibition of linoleic acid oxidation and thiobarbituric acid test an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
43
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 53 publications
9
43
1
2
Order By: Relevance
“…The amounts of TPC in GME, GEE, GCE, and GMO signifi cantly (p < 0.05) increased from 1.96, 1.85, 1.17, and 0.91 mg GAE/g in an unroasted control to 3.41, 3.23, 2.01, and 1.64 mg GAE/g in 7.5 min roasted groundnut samples respectively. A similar trend was reported by Win et al (2011) for oven-roasted peanut extracts. Pandey and Awasthi (2015) also reported that roasting increased the total phenolic content in fenugreek seeds.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The amounts of TPC in GME, GEE, GCE, and GMO signifi cantly (p < 0.05) increased from 1.96, 1.85, 1.17, and 0.91 mg GAE/g in an unroasted control to 3.41, 3.23, 2.01, and 1.64 mg GAE/g in 7.5 min roasted groundnut samples respectively. A similar trend was reported by Win et al (2011) for oven-roasted peanut extracts. Pandey and Awasthi (2015) also reported that roasting increased the total phenolic content in fenugreek seeds.…”
Section: Resultssupporting
confidence: 89%
“…The changes in antioxidative activity and phenolic content, which occur during the conventional oven roasting (Craft et al, 2010;Davis et al, 2010;Win et al, 2011) of groundnuts (Arachis hypogaea L.) have been well investigated. To the best of our knowledge, nothing has been reported on the eff ect of microwave roasting on the antioxidative activity and phenolic content of the seeds of the groundnut cultivar developed in Bangladesh, which is the main objective of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…After 3 min MW cooking, the samples showed a TPC of 4.52 mg TAE/g or more: PMW (8.94 mg TAE/g) > PEW (7.54 mg TAE/g) > PME (6.42 mg TAE/g) > PEE (5.70 mg TAE/g) > PMO (4.52 mg TAE/g). A similar trend was found by Ali et al (2016a) for microwaved groundnut, and by Win et al (2011) for oven-roasted peanut. The roasting process most likely increased the TPC through the following mechanisms: roasting might partially destroy the cell structure, resulting in the release of some bound phenolic compounds, which could then become more extractable in aqueous ethanol and acetone (Zou et al, 2015).…”
Section: Changes In Antioxidant Activitysupporting
confidence: 82%
“…It has been revealed that the optimum roasting time was essential for enhancing the antioxidant capacity and phenolics concentration in peanut kernel flour Win et al (2011).…”
Section: Introductionmentioning
confidence: 99%